Endotoxin in vitro interactions with human neutrophils: depression of chemiluminescence, oxygen consumption, superoxide production, and killing. - Proctor, R A (1979)
Endotoxin was shown to depress neutrophil bactericidal activity while enhancing Nitro Blue Tetrazolium reduction and hexose monophosphate shunt activity. Separation of bactericidal action from oxidative metabolism suggests that the effect of endotoxin might involve the formation of reactive oxygen radicals such as superoxide. Chemiluminescence often accompanies metabolic activation of polymorphonuclear neutrophils (PMNs). However, human PMNs did not show chemiluminescence when challenged with endotoxin (lipopolysaccharide; LPS) or lipid A. Superoxide formation was also unaffected by endotoxin. In contrast, preincubation of PMNs with LPS for 30 min produced significant depression of chemiluminescence, oxygen consumption, and superoxide formation. Decreased chemiluminescence was not the result of complement consumption. In a cell-free system, superoxide was not scavenged by LPS, nor did LPS stimulate superoxide dismutase. Oxidase enzymes for reduced nicotinamide adenine dinucleotide or reduced nicotinamide adenine dinucleotide phosphate harvested from broken cells were not affected by LPS. The toxicity of LPS may reside in its ability to activate the PMNs while simultaneously blocking bactericidal capacity.